2015
DOI: 10.1007/s00221-015-4403-9
|View full text |Cite
|
Sign up to set email alerts
|

Relative errors can cue absolute visuomotor mappings

Abstract: When repeatedly switching between two visuomotor mappings, e.g. in a reaching or pointing task, adaptation tends to speed up over time. That is, when the error in the feedback corresponds to a mapping switch, fast adaptation occurs. Yet, what is learned, the relative error or the absolute mappings? When switching between mappings, errors with a size corresponding to the relative difference between the mappings will occur more often than other large errors. Thus, we could learn to correct more for errors with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Second, and more generally, learning “classes” of commonly encountered tool transformations, that can be refined rapidly to particular circumstances, simplifies the otherwise seemingly intractable problem of needing as many learned mapping states as there are tools that we use. These accounts make different predictions for the generalizability of experience with different tools, and for learning novel tool mappings (van Dam and Ernst 2015b). …”
Section: Discussionmentioning
confidence: 99%
“…Second, and more generally, learning “classes” of commonly encountered tool transformations, that can be refined rapidly to particular circumstances, simplifies the otherwise seemingly intractable problem of needing as many learned mapping states as there are tools that we use. These accounts make different predictions for the generalizability of experience with different tools, and for learning novel tool mappings (van Dam and Ernst 2015b). …”
Section: Discussionmentioning
confidence: 99%
“…In the literature, most of the existing methods adopt loss functions built on absolute error criteria, with the most popular including the least squares (LS) and least absolute deviation (LAD). Under certain settings, it has been found that the relative errors are more sensible [8,12,16]. The most distinguishable feature of the relative error-based approaches is that they are scale-free, which, as discussed in the published studies [3], can be advantageous in survival and other analysis.…”
Section: Introductionmentioning
confidence: 99%